Pippi goes to school - Lindgren, Astrid, 1907-2002.; Chesworth, Michael (New York : Puffin Books, 1999)
After Tommy and Annika entice Pippi into going to school, her first-and-only day there is unlike anything they ever expected.
Text excerpted from two chapters of Pippi Longstocking.
Translated from the Swedish.
L.A. Recommended Foreign Language
L.A. Recommended Foreign Language, February 2000
4.6
K-3.
Keywords: First day of school -- Fiction; Humorous stories; Schools -- Fiction; First day of school -- Fiction; Humorous fiction; School stories; Sweden -- Fiction; Sweden -- Fiction